Cross Border Carbon Trading and the Principle of Climate Justice: An Analysis of the Implementation of the Paris Agreement (A Comparative Study of Indonesia and India) - Ade Putra Hasibuan; Eva Aini; Vinay Kumar Yadav (Recht Studiosum Law Review, 2026)
The climate crisis cannot be resolved simply by reducing global emissions, it must also be addressed equitably. The climate crisis is the result of economic development focused on growth without regard for the Earth's capacity. This article analyzes the implementation of the Paris Agreement on cross border carbon trading and the principles of climate justice between Indonesia and India, as well as the challenges of their enforcement. This research uses a normative juridical method with a library research approach, examining various international and national legal instruments such as the Paris Agreement, laws governing carbon emission use and equitable justice for both countries as well as their impacts. The results indicate that quantifying carbon emission reductions requires legal reform related to carbon trading regulations. The current regulation, Presidential Regulation Number 98 of 2021, lacks technical regulations. This makes it difficult to take progressive steps regarding carbon trading. The issue of legal certainty is also evident in the enactment of the Presidential Regulation. The legal form of the Presidential Regulation still only involves the Government in drafting the regulations, and this is very easy to change at any time. For the sake of legal certainty in regulating carbon trading in the future, consideration must be given to harmonizing and amending laws governing aspects of carbon trading, particularly the Environmental Law, the Forestry Law and the Regional Government Law, by incorporating aspects of justice for the community so that justice for the community, both inter and intra generational, can be realized. India's updated NDC represents the country's transition framework building requires to a path than that Western countries to achieve emission and is assistance advanced technology financing will need substantial its.